1996
DOI: 10.1002/(sici)1098-1071(199608)7:4<239::aid-hc5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dissociation of ylidyl chlorophosphanes

Abstract: The ylidyl substituent of the chlorophosphane Ph3P(DOUBLE BOND)CAr(SINGLE BOND)PRCl exerts a strong influence on the P(SINGLE BOND)Cl bond. An X‐ray structure investigation of the representative with Ar(DOUBLE BOND)Ph, R(DOUBLE BOND)Me reveals the longest P(SINGLE BOND)Cl bond ever observed for an acyclic chlorophosphine (226.2(1) pm). It is connected to a conformation that allows an effective negative hyperconjugation. The ylidyl chlorophosphanes with an amino group R are covalent in benzene but become more o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Detailed 31 P NMR studies of 1 a and 1 c revealed that this is not the case: d 31 P values vary only insignificantly over a large range of temperatures ( 30 to À 80 8C) and concentrations (0.02 to 1m), and spectra recorded at low temperatures gave no evidence for dynamically induced line broadening, which had been observed for other PÀCl bond-dissociation equilibria. [29] The nature of the PÀX bonds in P-fluoro and P-chlorodiazaphospholenes was further illuminated by studies of halogen NMR spectra of 1 a, 1 c, 3 a, and 6 a. The covalent character of the P À F bond in 6 a follows directly from the large scalar coupling ( 1 J PF 1070 Hz) between both nuclei.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed 31 P NMR studies of 1 a and 1 c revealed that this is not the case: d 31 P values vary only insignificantly over a large range of temperatures ( 30 to À 80 8C) and concentrations (0.02 to 1m), and spectra recorded at low temperatures gave no evidence for dynamically induced line broadening, which had been observed for other PÀCl bond-dissociation equilibria. [29] The nature of the PÀX bonds in P-fluoro and P-chlorodiazaphospholenes was further illuminated by studies of halogen NMR spectra of 1 a, 1 c, 3 a, and 6 a. The covalent character of the P À F bond in 6 a follows directly from the large scalar coupling ( 1 J PF 1070 Hz) between both nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…The spectroscopic and conductometric studies as well as the investigation of Lewis acid/base equilibria indicate that 2-chlorodiazaphospholenes dissociate in solution only to a small extent and that a spontaneous cleavage of PÀX bonds, as in ylide-substituted chlorophosphanes [29,45] is not observed. Even if this result contradicts earlier conjectures, [13,16] it complies with the higher stabilities of ylidyl-phosphenium ions as compared with diazaphospholenium cations.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (at 400 MHz) and ppm. 13 C NMR (at 100 MHz) chemical shifts are reported in ppm downfield of internal tetramethylsilane. 31 P NMR (at 162 MHz) chemical shifts are externally referenced to 85 % H 3 PO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with these observations, the phosphorus atom in 1a shows clear pyramidal geometry (more sp 3 -like); the sum of the three angles at P1 is only 295.3°. [13] Fe1-least-squares plane(C3-C7) 1.640(5), Fe1-leastsquares plane(C8-C12) 1.649(5); C1-P1-C7 88.7(1), C1-P1-C13 101.7(1), C7-P1-C13 104.9(1), dihedral angle between least-squares plane(C1-C7) and least-squares plane(C8-C12) = 0.29 (10).…”
Section: Characterization Of Phosphole (S)-1amentioning
confidence: 99%
“…So far the 2,4,6-triisopropylphenyl-and the tritertbutylphenylphospholes (1a and 1b) have been characterized by Bird indexes (BI) [13] of 40.4 [2] and 56.5 [3], respectively, based on the bond equalizing in the hetero ring. For arylphospholes 1a and 1b, the sum of the angles at the phosphorus atom, introduced by Schmidpeter as the measure of flattening [14], was found to be 314.4 [2] and 331.7 [3], respectively. For phospholes with pyramidal geometry at P, this number is around 302 [15].…”
mentioning
confidence: 99%